Reification of Bourgeois Ideology in Bhattarai’s Muglan - Bimal Kishore Shrivastwa (Journal of Language and Literature, 2022)
This paper aims to explore how innocent Nepali youths reify the elitist bourgeois ideology of the Nepalese society that forces them to go to Muglan, a term, denoting foreign country for Nepali people, and confront unexpected blows there in Govinda Raj Bhattarai’s novel, Muglan. Reification signifies the ideology and perception of people residing in a capitalist society. The study of the impact of reification demonstrates the reality of a society. Bhattarai is critical to the way Sutar Kanchha, the protagonist of the novel, obsessed with the dominant capitalist ideology, goes to Bhutan to earn. But he gets robbed there and he is forced to do tough physical labor like an animal. To survey terrific effects of the dominant capitalist ideology of the Nepalese society over the life of the poor Nepali people, the research paper applies neo-Marxist insights, with special focus on Louis Althusser and Antonio Gramsci. The chief finding is that Bhattarai is critical to persisting capitalist ideology of the Nepalese society that forces innocent Nepali youths to leave their country just for survival. But, in turn, they get robbed and are compelled to work like slaves in the cruel Muglan. It is expected that researchers intending to explore on Nepali literature from the neo-Marxist perspective will find the paper a useful reference.